Photoisomerization and Photochemistry of Matrix-Isolated 3-Furaldehyde - Kuş, Nihal (2010)
3-Furaldehyde (3FA) was isolated in an argon matrix at 12 K and studied using FTIR spectroscopy and quantum chemistry. The molecule has two conformers, with trans and cis orientation of the O═C—C═C dihedral angle. At the B3LYP/6-311++G(d,p) level of theory, the trans form was computed to be ca. 4 kJ mol−1 more stable than the cis form. The relative stability of the two conformers was explained using the natural bond orbital (NBO) method. In fair agreement with their calculated relative energies and the high barrier of rotamerization (ca. 34 kJ mol−1 from trans to cis), the trans and cis conformers were trapped in an argon matrix from the compound room temperature gas phase in proportion 7:1. The experimentally observed vibrational signatures of the two forms are in a good agreement with the theoretically calculated spectra. Broad-band UV-irradiation (λ > 234 nm) of the matrix-isolated compound resulted in partial trans → cis isomerization, which ended at a photostationary state with the trans/cis ratio being ca. 1.85:1. This result was interpreted based on results of time-dependent DFT calculations. Irradiation at higher energies (λ > 200 nm) led to decarbonylation of the compound, yielding furan, cyclopropene-3-carbaldehyde, and two C3H4 isomers: cyclopropene and propadiene.